2009
DOI: 10.1063/1.3255016
|View full text |Cite
|
Sign up to set email alerts
|

Contact resistance between metal and carbon nanotube interconnects: Effect of work function and wettability

Abstract: The contact resistance of 14 different electrode metals with the work function between 3.9 and 5.7 eV has been investigated for carbon nanotube (CNT) interconnects. We observed that the contact resistance was mainly influenced by the two following parameters: the wettability and the work function difference of electrode metal to CNT. Ti, Cr, and Fe with good wettability showed lower resistance than other metals. Furthermore, no dependence of the contact resistance on the work function difference has been obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(114 citation statements)
references
References 28 publications
2
108
3
Order By: Relevance
“…The 3D electrostatics accounts of the full device geometry: the SWNTs on the quartz substrate are terminated by source (S) and drain (D) contacts, and covered by insulating material Tc-resist. The results show that carrier transport depends sensitively on (i) the diameter of the tubes within the as-growth array, (ii) the work-function of the contact materials (Pd (5.1 eV), Au (5.0 eV), Mo (4.6 eV), Ti (4.33 eV), Al (4.1 eV), and Mg (3.7 eV)) 40,54,59 and (iii) effective applied bias, V DS (extracted by correlating the equivalent trench depths in Tc-resist for DC and microwave inputs). The source to drain of this two-terminal device is separated by L 0 ¼ 15 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D electrostatics accounts of the full device geometry: the SWNTs on the quartz substrate are terminated by source (S) and drain (D) contacts, and covered by insulating material Tc-resist. The results show that carrier transport depends sensitively on (i) the diameter of the tubes within the as-growth array, (ii) the work-function of the contact materials (Pd (5.1 eV), Au (5.0 eV), Mo (4.6 eV), Ti (4.33 eV), Al (4.1 eV), and Mg (3.7 eV)) 40,54,59 and (iii) effective applied bias, V DS (extracted by correlating the equivalent trench depths in Tc-resist for DC and microwave inputs). The source to drain of this two-terminal device is separated by L 0 ¼ 15 mm.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that interaction energies of transition metals enhance with the number of vacancies in d orbital. If the vacancy is the same, the closer to the nucleus the d orbital is, the higher the interaction energy is, [14]. We can confer that the 3d metal of Ti possesses higher interaction energy than the 5d metal of Hf, even though they have the same number of vacancies in d orbital.…”
Section: Theory and Considerationmentioning
confidence: 71%
“…111 The possible application of VANTAs and VACNFs as microelectronic interconnects has driven many studies to characterize their end-contact quality. 71,[111][112][113][114][115] The reported end-contact resistances vary significantly from one measurement to another suggesting a wide spectrum of influencing parameters. Important parameters are the surface roughness of the metal underlayer as well as its surface oxidation, 115 the wettability of the metal underlayer and its work function, 112 and the growth conditions.…”
Section: Quality Factormentioning
confidence: 99%
“…71,[111][112][113][114][115] The reported end-contact resistances vary significantly from one measurement to another suggesting a wide spectrum of influencing parameters. Important parameters are the surface roughness of the metal underlayer as well as its surface oxidation, 115 the wettability of the metal underlayer and its work function, 112 and the growth conditions. 111 In general, the magnitude of the reported contact resistances for an individual interface is in the order of a few to tens of kilo ohms.…”
Section: Quality Factormentioning
confidence: 99%